ECONOMETRIC ANALYSIS OF INDUSTRIAL SECTOR DEVELOPMENT AND FORECASTING MODELS (International scientific-electronic journal “Pioneering studies and theories”, 2026)
This study examines the econometric analysis of industrial sector development and proposes forecasting models to assess future growth trajectories. The research focuses on identifying key determinants of industrial performance, including investment inflows, labor productivity, technological intensity, and structural transformation. Using modern econometric techniques, the study evaluates the relationship between industrial output and macroeconomic indicators. Trend analysis, multiple regression modeling, and scenario-based forecasting approaches are applied to estimate short- and medium-term industrial growth prospects. The findings demonstrate that investment intensity, innovation capacity, and structural diversification significantly influence industrial development. The proposed forecasting models provide a reliable analytical framework for evidence-based industrial policy formulation and strategic economic planning.